Characterization and Disease Severity of Pathogenic Microbes on 20 Red Chili Genotypes - Tunjung Pamekas; Dwi Wahyuni Ganefianti; Nelly Destinawati (Jurnal Ilmu Pertanian Indonesia, 2023)
Pathogenic microbes are the limiting factor in increasing red chili productivity. These pathogens cause decreasing yield of red chili up to 50-100%. This research aimed to characterize and evaluate disease severity on 20 red chili genotypes caused by pathogenic microbes. The research was arranged in Randomized Complete Block Design with three replications. The samples were 20 chili genotypes, namely UNIB K01, UNIB CGTS1, G35, G48, G56, G60, G67, G77, and G43 (developed by the University of Bengkulu researchers) and IPB C19, COPAY, IPB C495, IPB C14, DORSET NAGA, IPB C4, IPB PANJANG, LOKAL BENGKULU, SELOKA, SSP, and ANIES (developed by others). The results showed that four groups of pathogens attacked red chili, namely Fusarium oxysporum, which causes fusarium wilt disease; Cercospora sp., the cause of leaf spot disease; Colletotrichum sp. causes anthracnose; and virus groups. All tested red chili genotypes could be infected by these four pathogens in which the incubation period, disease incidence, and disease severity were insignificant. Of the nine genotypes developed by the University of Bengkulu researchers, the G35 genotype had the best potency to be developed as a disease-resistant genotype. Keywords: Cercospora sp, Colletotrichum sp, Fusarium s, virus